2017
DOI: 10.1016/j.jvs.2016.05.088
|View full text |Cite
|
Sign up to set email alerts
|

Repeated contrast medium application after endovascular aneurysm repair and not the type of endograft fixation seems to have deleterious effect on the renal function

Abstract: Our study showed no significant difference in renal impairment between SR and IR fixation in EVAR for IR abdominal aortic aneurysm. However, significantly more renal deterioration was observed in patients with increased postoperative contrast medium expose. Therefore, alternatives such as contrast- enhanced duplex ultrasound or magnetic resonance imaging for EVAR surveillance should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In a previous study, we demonstrated the effect of CA volume on renal deterioration regardless of the type of stent graft fixation used. 9 The small difference in CA volume used intraoperatively probably has little or no effect on renal function compared with multiple preoperative and postoperative applications of iodinated CA, which has been linked to a decline in renal function 10 and indirectly with survival rates. 11 However, we believe a reduction in need of intraoperative CA can improve the perioperative outcome, especially in fragile patients, or by treatment of complications that further increase the need of CA.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated the effect of CA volume on renal deterioration regardless of the type of stent graft fixation used. 9 The small difference in CA volume used intraoperatively probably has little or no effect on renal function compared with multiple preoperative and postoperative applications of iodinated CA, which has been linked to a decline in renal function 10 and indirectly with survival rates. 11 However, we believe a reduction in need of intraoperative CA can improve the perioperative outcome, especially in fragile patients, or by treatment of complications that further increase the need of CA.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-induced kidney injury can also lead to long-term deficits in kidney function. 15 Chronically, nonocclusive issues such as kinking can occur in renal stents, resulting in worsening renal function over the longer term. In our fenestrated group, two patients experienced renal stent thrombosis (of a total 32 patients [6.25%] with 94 branch vessels [2.1%] treated), likely related to severe angulation of the paravisceral aorta in one and severe angulation at the interface with the aortic stent of the affected renal artery in the second.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, medium use of contrast during EVAR has been reported somehow higher (median contrast medium used 120 ml). 15…”
Section: Discussionmentioning
confidence: 99%